Do Virtual Team Members Swim Against the Tide? - Shwartz-Asher, Daphna; Ahituv, Niv (Current Overview on Science and Technology Research Vol. 5, 2022)
Since the outbreak of the Covid-19 pandemic, the phenomenon of distance working has rapidly increased and examining cooperation between members of virtual teams is of great importance. The aim of this study, therefore, was to specifically investigate compliance of team members in the digital, virtual setting. We hypothesized that members of structured virtual teams will show lower degrees of compliance compared to members of structured non-virtual teams. To test this hypothesis, we examined the impact of virtual team characteristics on team members’ compliance with instructions. In our experiment, 150 subjects were given a set of instructions for conducting a task in a virtual or non-virtual team setting. The main finding of this study, which were not in line with our hypotheses, indicates that members of virtual teams exhibited a higher degree of compliance with directives than members of non-virtual teams. It is possible that this difference stems, at least in part, from the formality variable that was stronger in the virtual setting. This study conclusions adds to the pool of knowledge on virtual teams and could enhance virtual team leaders’ ability to effectively lead their teams.